AgQDs employing black box synthetic strategy: photocatalytic and biological behavior - Pansare, Amol V.; Shedge, Amol A.; Chhatre, Shraddha Y.; Das, Debabrata; Murkute, Punam; Pansare, Shubham V.; Nagarkar, Amit A.; Patil, Vishwnath R.; Chakrabarti, S. (Journal of Luminescence, 2019)
This investigation relates FRET, photocatalytic and a biological study of AgQDs which found to be dependent on particle size and capping agent used. Surface of AgQDs was one of the most important factors that govern its activity. AgQDs with BSA binding was systematically studied by fluorescence quenching and electrostatic interaction. AgQDs mainly interacted to site II of BSA, binding distance r evaluated according to the FRET theory and was 4.6 nm for AgQDs, which suggested transfer of energy (non-radioactive) between surface modified AgQDs and biological molecule BSA. The photocatalytic activity of AgQDs for the appreciable degradation of erythrosine dye using Ultraviolet-B light was investigated. AgQDs showed specific antibacterial activity against E. coli bacterial stain. Quantum dots displayed a pronounced and specific activity causing > 50% growth of COLO-205 and MCF-7 human cancer Cells at concentrations < 10(-7 )M. Hence, present black box synthetic protocol of AgQDs could be life science application.
Keywords: AgQDs; Black box; COLO-205; Photocatalytic